Atomic physics - Born, Max, 1882-1970 (Dover books on physics and chemistry, 1989)
The Nobel Laureate's brilliant exposition of the kinetic theory of gases, elementary particles, the nuclear atom, wave-corpuscles, atomic structure and spectral lines, electron spin and Pauli's principle, quantum statistics, molecular structure and nuclear physics. Over 40 appendices, a bibliography, numerous figures and graphs.